“Mon prince charmant parle coréen : les fans de K-Pop en France et Lituanie”, - Jeong-Im HYUN (De Boeck Supérieur, 2022)
For several years now, K-Pop became increasingly popular in the West, even in a small country like Lithuania. One explanation of K-Pop’s popularity is the Korean government investment in popular cultural products as part of a wider strategy of achieving soft power in the international political arena. However I argue in this paper that this point of view is too narrow to understand the global K-Pop phenomena. To understand ‘why’ and ‘how’ an increased number of Westerners (Europeans) have become K-Pop fans, on the basis of field work carried out in both France and in Lithuania, I argued that K-Pop fans in these two countries have followed a similar path to arrive at K-Pop: they have been influence by Japanese popular culture and have in general held a fascination for East Asian culture, and have used the Internet to satisfy their tastes and desires. The K-Pop phenomena shows us that the origins of our individual desire is contagious. As such, contagion means that a particular cultural form could gain global popularity relatively quickly, but its popularity could be short in duration.